TI_GERICHTE 15.2020.119 vom 14. Dezember 2020 , Ricorsi contro un avviso di pignoramento e una comminatoria di fallimento - TI Tribunale d'appello (2020)
Ricorsi contro un avviso di pignoramento e una comminatoria di fallimento